Identifying the most critical behavioral lifestyles associated with MAFLD: evidence from the NHANES 2017–2020 - Li, Sicheng; Chen, Jiajin; Zhang, Yuqin; Huang, Shourui; Pan, Qing; Tang, Dan; Lan, Tianjiao; Bu, Shichen; Wang, Yan (Frontiers in Endocrinology, 2024)
Per interquartile-quartile range increases in sleep duration (OR=0.883, 95% CI: 0.826--0.944), MET (0.916, 0.871--0.963), and HEI-2015 score (0.827, 0.756--0.904) were significantly associated with MAFLD. The joint exposure of sleep duration, MET, and HEI-2015 score was associated with MAFLD (0.772, 0.688--0.865), with the highest weight (importance) for MET (0.526). PAFs revealed highergreater intervention benefits for sleep and the HEI-2015 when the majority populationsof the population (>5%) were defined ashad a low MAFLD risk (weak intervention targets), whereas MET iswas the moremost efficient intervention strategy when minority populations (≤5%) were defined ashad a low MAFLD risk (strong intervention targets). Conclusion: TheThis study founddemonstrated significant associations of between MAFLD and single and joint exposures ofto sleep duration, MET, and HEI-2015 with MAFLD and identified physical activity as the most important lifestyle factor. Further population benefit analyses may provide evidence and suggestions for population-level interventions.